Pelaksanaan Advance Medical Directive (AMD): tinjauan dari perspektif maslahah / Muhamad Sayuti Mansor, Muhammad Safwan Harun dan Muhammad Ikhlas Rosele - Mansor, Muhamad Sayuti; Harun, Muhammad Safwan; Rosele, Muhammad Ikhlas (Universiti Teknologi MARA, Pulau Pinang & Pusat Penerbitan Universiti (UPENA), 2016)
The development of knowledge in the field of medicine in Malaysia in something that is well known. This occurs as the result of the development in science and technology that spread globally nowadays. This development also become the basis that spark many moral questions as well as Islamic jurisprudential issues, until the fiqh of medicine becomes among the subject of discussion and research interest to the Muslim intellectual today. Among these issues are the Advance Medical Directive (AMD). AMD is a legal document that was made by an individual to outline his wishes and preferences in regard to medical treatments and interventions in the event that he becomes terminally ill and unconscious. The AMD inflicted the question whether it is permissible or go against the sharia. So, this study was conducted using the qualitative approach to analyse the position of AMD from the perspective of maslahah. This study shows that AMD is permissible in the sharia but in some conditions it must refers to the maslahah perspective to execute or null any wishes and preferences that was made in the AMD.